Urticarial reaction following endovascular embolization of an orbital arteriovenous malformation (AVM) with n-butyl cyanoacrylate (nBCA) glue. Issue 6 (December 2017) - Sinha, Kunal R; Duckwiler, Gary; Rootman, Daniel B
Orbital arteriovenous malformations (AVMs) are rare vascular lesions that may be managed with endovascular embolization followed by surgical resection. Embolization is often accomplished with n-butyl-2-cyanoacrylate (nBCA), which is considered to be a safe and effective liquid occlusive agent. Localized vascular inflammation has been associated with endovascular nBCA use in histopathologic studies, but reports of systemic hypersensitivity reactions following endovascular embolization with nBCA are rare. We present a case of a 26-year-old male who developed an intermittent systemic urticarial reaction without cardiopulmonary compromise beginning four weeks after nBCA embolization of an orbital AVM. Subsequent skin allergy testing performed by an allergist confirmed hypersensitivity to nBCA glue and the patient has since been successfully managed with daily oral antihistamines. Awareness of this rare potential complication of endovascular embolization with nBCA will aid in the counseling and management of patients with AVMs.